Peranan Kerapatan Adat Nagari dalam Menyelesaikan Sengketa Tanah Ulayat di Kenagarian Koto Tangah Kecamatan Tanjung Emas Kabupaten Tanah Datar - Rezki Pratama, Fauzan; Magriasti, Lince (Policy, Law and Political Research Center, 2024)
Customary land disputes are one of the problems that often occur in Indigenous communities, including in Nagari Koto Tangah, Tanjung Emas District, Tanah Datar Regency. Nagari Traditional Density (KAN) is an important element in the Minangkabau Indigenous community. Kerapatan Adat Nagari (KAN) is a traditional institution that functions to resolve various problems in traditional communities, including customary land disputes. This research aims to analyze the role of the Nagari Customary Association (KAN) in resolving customary land disputes in Nagari Koto Tangah, Tanjung Emas District, Tanah Datar Regency. This research uses qualitative research with an empirical juridical approach. The qualitative research method was chosen because this research aims to understand the role of the Nagari Traditional Village (KAN) in resolving customary land disputes in depth. The results of the research show that the Nagari Customary Meeting has an important role in resolving customary land disputes in Nagari Koto Tangah, Tanjung Emas District, Tanah Datar Regency. The Nagari customary meeting acts as a mediator, arbitrator, alternative resolution. The Nagari Customary Meeting has several advantages: it is faster in resolving problems, more fair and wiser, and maintains harmony better. This research provides suggestions so that the Nagari Customary Association continues to be empowered as an institution for resolving customary land disputes in the Minangkabau traditional community.